Establishment of a Macaca fascicularis gut microbiome gene catalog and comparison with the human, pig, and mouse gut microbiomes. Issue 9 (18th August 2018) - Li, Xiaoping; Liang, Suisha; Xia, Zhongkui; Qu, Jing; Liu, Huan; Liu, Chuan; Yang, Huanming; Wang, Jian; Madsen, Lise; Hou, Yong; Li, Junhua; Jia, Huijue; et al.
Abstract: Macaca fascicularis, the cynomolgus macaque, is a widely used model in biomedical research and drug development as its genetics and physiology are close to those of humans. Detailed information on the cynomolgus macaque gut microbiota, the functional interplay between the gut microbiota and host physiology, and possible similarities to humans and other mammalians is very limited. The aim of this study was to construct the first cynomolgus macaque gut microbial gene catalog and compare this catalog to the human, pig, and mouse gut microbial gene catalogs. We performed metagenomic sequencing on fecal samples from 20 cynomolgus macaques and identified 1.9 million non-redundant bacterial genes of which 39.49% and 25.45% are present in the human and pig gut bacterial gene catalogs, respectively, whereas only 0.6% of the genes are present in the mouse gut bacterial gene catalog. By contrast, at the functional levels, more than 76% Kyoto Encyclopedia of Genes and Genomes orthologies are shared between the gut microbiota of all four mammalians. Thirty-two highly abundant bacterial genera could be defined as core genera of these mammalians. We demonstrated significant differences in the composition and functional potential of the gut microbiota as well as in the distribution of predicted bacterial phage sequences in cynomolgus macaques fed either a low-fat/high-fiber diet or a high-fat/low-fiber diet. Interestingly, the gut microbiota of cynomolgus macaques fed the high-fat/low-fiber diet became more similar to the gut microbiota of humans.